Interactional Sociolinguistics: A Comparative Analysis of Contextual Miscommunication in British / American and Nigerian Institutional Discourse - Evughaye, Joseph Erhovwojese (NIU Journal of Humanities; Vol 10 No 4 (2025): NIU Journal of Humanities, Vol. 10 No. 4, December 2025, 2025)
This paper examines the vital role context plays in Interactional Sociolinguistics (IS) especially as it relates to cross-cultural miscommunications exemplified in British/American and Nigerian data. This study, therefore, critically investigates the intricate dynamics of how context shapes interactional communication, highlighting how cross-cultural differences, linguistic norms and societal expectations and contextualization cues often lead to semantic misrepresentation, misunderstandings and miscommunications. Drawing on empirical data from complex and linguistically diverse cultural background, the study demonstrates how Gumperz IS and contextualization theories can lighten-up the complex interplay between language, culture and context in cross-cultural sociolinguistic interactions. The study drew from purposively selected structured interviews involving electricians, bricklayers, teacher/pupils exchange and Head of Department/staff conversations, which were subjected to discourse analysis. The data reflect work environment across different regions, including USA, UK and Nigeria. The findings reveal that language is consequential in sociocultural context in which communication takes place, and also brings to the fore that effective cross-cultural communication requires not only linguistic competence but also a deep understanding of the cultural nuances and contextual factors that shape interactional dynamics. This paper also contributes to the unburdening of age-long perception that pragmatic context alone rather than cross-cultural differences often lead to miscommunication and distortion of intended meaning in interactional communication in an increasingly globalized world. Keywords: Interactional Sociolinguistics, Cross-Cultural Miscommunication, Contextualization Cues, Context, Cultural Differences.